1993
DOI: 10.1136/ard.52.9.643
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal plasma fibrinolysis in patients with rheumatoid arthritis and impaired endothelial fibrinolytic response in those complicated by vasculitis.

Abstract: Objectives-(a) To assess plasma fibrinolytic parameters in patients with rheumatoid arthritis (RA) and to determine whether there are differences between patients with RA alone and those with RA complicated by vasculitis. (b) To determine if patients with RA respond differently to venous occlusion compared with normal subjects and to assess whether such a response differs in patients with RA alone and those with rheumatoid vasculitis. (c) To determine the extent of vascular damage in patients with rheumatoid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…These findings are consistent with previous data, especially among those with vasculitis [11,12], perhaps reflecting increased release due to direct endothelial injury. Recently, a link between vWF and ultrasonographic carotid intima thickness (IMT, an indirect marker of coronary disease) in RD was reported [13], although a previous study reported no such correlation in 39 patients with established RD [14].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with previous data, especially among those with vasculitis [11,12], perhaps reflecting increased release due to direct endothelial injury. Recently, a link between vWF and ultrasonographic carotid intima thickness (IMT, an indirect marker of coronary disease) in RD was reported [13], although a previous study reported no such correlation in 39 patients with established RD [14].…”
Section: Discussionsupporting
confidence: 94%
“…Of the fibrinolytic factors assayed, increased tissue plasminogen activator (tPA) was noted in one study [8], but not in another [16]. Similar findings have been observed with plasminogen activator inhibitor (PAI) [8,16,78]. Levels of PAI and tPA independently predicted cardiac events in 74 seropositive patients [41].…”
Section: Thrombogenesissupporting
confidence: 55%
“…In the RA joints, accumulation of fibrin is thought to result from an altered balance between coagulation and fibrinolysis. It could contribute to chronicity and progressivity of the disease through the proinflammatory and degradative effects of various factors participating in and resulting from its formation and elimination (31)(32)(33)(34)(35)(36). A more disease-specific role for fibrin in the pathogenesis of RA is very probably through its action as an autoantigen and perhaps as an immunogen.…”
Section: Discussionmentioning
confidence: 99%